Sr2+ induces unusually stable d(GGGTGGGTGGGTGGG) quadruplex dimers. Issue 11 (November 2016) - Lomidze, Levan; Kelley, Sean; Gogichaishvili, Shota; Metreveli, Nunu; Musier‐Forsyth, Karin; Kankia, Besik
Abstract: Guanine‐rich sequences are able to form quadruplexes consisting of G‐quartet structural units. Quadruplexes play an important role in the regulation of gene expression and have therapeutic and biotechnological potential. The HIV‐1 integrase inhibitor, (GGGT)4, and its variants demonstrate unusually high thermal stability. This property has been exploited in the use of quadruplex formation to drive various endergonic reactions of nucleic acids such as isothermal DNA amplification. Quadruplex stability is mainly determined by cations, which specifically bind into the inner core of the structure. In the present work, we report a systematic study of a variant of the HIV‐1 integrase inhibitor, GGGTGGGTGGGTGGG (G3T), in the presence of alkali and alkaline‐earth cations. We show that Sr 2+ ‐G3T is characterized by the highest thermal stability and that quadruplex formation requires only one Sr 2+ ion that binds with low micromolar affinity. These concentrations are sufficient to drive robust isothermal quadruplex priming DNA amplification reaction. The Sr 2+ ‐quadruplexes are also able to form unusually stable dimers through end‐to‐end stacking. The multimerization can be induced by a combination of quadruplex forming cations (i.e., K + or Sr 2+ ) and non‐specific Mg 2+ .